2008
DOI: 10.1021/jp803192u
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Self-Assembly Processes Driven by Nonbonded Interactions in Soft Materials

Abstract: This Centennial Feature Article provides an overview of research in the general area of self-assembly modeling, with particular emphasis on the self-assembly of molecules into soft nanoscale structures where the driving force for assembly is provided by nonbonded interactions (hydrogen bonds and electrostatics). The models have been developed at many different levels of theory, going all the way from simple analytical models of packing effects to atomistic descriptions using molecular dynamics methods. In betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 122 publications
0
75
0
Order By: Relevance
“…A number of researchers have recently studied molecular selfassembly in a supramolecular materials context using computational approaches 27,28 . In previous work, we have shown that the propensity of dipeptides (two amino acids) to aggregate can be predicted using coarse-grain (CG) molecular dynamics (MD) 29 .…”
mentioning
confidence: 99%
“…A number of researchers have recently studied molecular selfassembly in a supramolecular materials context using computational approaches 27,28 . In previous work, we have shown that the propensity of dipeptides (two amino acids) to aggregate can be predicted using coarse-grain (CG) molecular dynamics (MD) 29 .…”
mentioning
confidence: 99%
“…There have been a plethora of experimental as well as simulation studies based on atomistic, coarse-grained (CG), simple bead and packing models to study the structure and self-assembly of peptides1011 and PA fibres157121314151617. In general, these studies were focused on understanding and exploiting the role of molecular interactions and secondary structure in PA self-assembly process.…”
mentioning
confidence: 99%
“…To probe this question, we developed a coarse-grained (CG) polyelectrolyte model of the SNA that provides the relationship between the radius of gyration ( R G ) of unhybridized anchored strands as a function of n (see Supporting Information for details). 14 Briefly, in this bead–spring CG model, we have explicitly included NaCl salt ions and a charged DNA backbone. The inclusion of ions has two main effects on the R G of strands—the presence of an ion profile of the SNA (Figure S7) as a function of n , and the exchange of ions between the bulk and SNA during hybridization—each of which has important effects on the Δ G of hybridization.…”
mentioning
confidence: 99%